Endoscopic submucosal tunnel dissection for large esophageal neoplastic lesions - Linghu, E.; Feng, X.; Wang, X.; Meng, J.; Du, H.; Wang, H. (Endoscopy, 2013)
Endoscopic submucosal dissection (ESD) has been widely used for resection of esophageal neoplastic lesions, but there are still technical challenges in treating large ones. Based on the development of tunneling technique, we report the first series in which the new technique of endoscopic submucosal tunnel dissection (ESTD) was used to remove large lesions in the esophagus. ESTD was attempted in five consecutive patients with esophageal lesions for which resection was indicated. In the operation, once the margin of the lesions had been marked, a submucosal tunnel was created by submucosal dissection from the oral incision to the anal incision. Bilateral resection was then performed to remove the lesion completely. The average length of the five lesions was 5.7 cm, and their extent as a proportion of the whole circumference of the lumen ranged from one third to four fifths. Operative time ranged from 50 minutes to 120 minutes (mean, 77 minutes). En bloc resection with negative lateral and basal margins was achieved in all lesions without complications.